Utilization of Local Wisdom to Overcome Malnutrition of Children in South Sorong Districts, West Papua Province, Indonesia - Gurendro Putro1 , Noor Edi Widya Sukoco1 , Erni Rosita Dewi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: In South Sorong Districts in 2013 there were 47.6% cases of malnourished and underweight children under five; short and very short toddler cases (stunting) of 60.7%. In 2017 South Sorong Districts was one of the 100 districts that were the priority in handling stunting problems. Where the problem of stunting is chronic malnutrition in the period ranging from uterus to toddlers. Purpose: this research aims to find the socio-cultural potential and local wisdom in overcoming nutritional problems in these children under five. Method: this riset mix methods by looking for quantitative and qualitative data. Quantitative data with anthroprometry and qualitative data conduct in-depth interviews and village community consultations in finding solutions that are appropriate to the conditions of the community. Result: It was found as many as 49.41% of malnutrition, while stunting was 54.1%. Natural potential in the form of food ingredients, fish, sea shrimp, chicken, sago and various vegetables already exists in the community. The community made an agreement in dealing with the nutritional problems of these children with child care, nutrition, nutrition and sanitation. Conclucion: that in handling nutritional problems of children there is involvement of the community, traditional leaders, religious leaders, support from the village head and the support of the regional government in the form of special team formation and additional budgets on children under five nutrition programs